The Properties of Fuel and Characterization of Functional Groups in Biodiesel -Water Emulsions from Waste Cooking Oil and Its Blends - Bhikuning, Annisa; Senda, Jiro Senda (Universitas Pendidikan Indonesia, 2020)
Studying biodiesel as an alternative fuel is important for finding the most suitable fuel for the future. Biodiesel from waste cooking oil is one of the alternative fuels to replace fossil oil. Waste cooking oil is the used oil from cooking and is taken from hotels or restaurants. The emulsion of waste cooking oil and water is produced by adding water to the oil, as well as some additives to bind the water and the oil. In this study, the fuel properties of 100% biodiesel waste cooking oilÂ are compared to several blends by volume: 5% of biodiesel waste cooking oil blended with 95% diesel oil (BD5), 10% of biodiesel waste cooking oil blended with 90% of diesel oil (BD10), 5% of biodiesel waste cooking oil blended with 10% of water and 18.7% of additives (BDW18.7), and 5% of biodiesel waste cooking oil blended with 10% of water and 24.7% of additives (BDW24.7). The objectives of this study are to establish the properties and characteristics of the FTIR (Fourier-transform infrared spectroscopy) of biodiesel-water emulsions from waste cooking oil and to compare them to other fuels. The chemical properties of the fuels are analyzed by using the ASTM D Method and FTIRÂ to determine the FAME (fatty acid methyl ester) composition of biodiesel in diesel oil. The results showed that the addition of additives in the water-biodiesel oil increases the viscosity, density, and flash point. However, it decreased the caloric value due to the oxygen content in the fuel.